2010
DOI: 10.1111/j.1464-410x.2010.09716.x
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor level in the prostatic fluid of patients with chronic prostatitis/chronic pelvic pain syndrome is correlated with symptom severity and response to treatment

Abstract: Study Type – Therapy (case series) Level of Evidence 4 OBJECTIVE To explore whether levels of nerve growth factor (NGF) in expressed prostatic secretions (EPS) are correlated with symptom severity in chronic prostatitis (CP) and chronic pelvic pain syndrome (CPPS). PATIENTS AND METHODS All patients with CP/CPPS underwent a complete history and physical examination, and were scored according to the National Institutes of Health Chronic Prostatitis Symptom Index (NIH‐CPSI). Expressed prostatic secretion sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 20 publications
3
48
0
4
Order By: Relevance
“…Several recent publications reported other biomarkers of CP. Watanabe et al [20] reported research from 20 cases, which revealed that nerve growth factor levels were significantly elevated in EPS from men with CPPS (NIH-III prostatitis) compared to controls. Wei et al [21] reported that the levels of B7-H3 were significantly lower in EPS from men with CPPS compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent publications reported other biomarkers of CP. Watanabe et al [20] reported research from 20 cases, which revealed that nerve growth factor levels were significantly elevated in EPS from men with CPPS (NIH-III prostatitis) compared to controls. Wei et al [21] reported that the levels of B7-H3 were significantly lower in EPS from men with CPPS compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the number of white blood cells in CNP rats, down regulate the expression of NF-κB, iNOS, ICAM-1, TNF-α, and inhibit the inflammatory reaction Turmeric [ 13] curcumin After intraperitoneal injection of curcumin in rats, the levels of IL-1β, TNF-α, MCP-1 and MIP-1α were reduced, and the peripheral nerves were repaired.…”
Section: Tripterygium Wilfordii Polyglycosidementioning
confidence: 99%
“…Researchers in Japan recently analyzed NGF levels expressed in the prostatic fluid of 20 patients with CP/CPPS before and after single, varied, 8-week treatment trials. These were compared to the NGF levels found in 4 asymptomatic control patients [28]. Before initiating treatment, men with CP/CPPS were found to have elevated NGF as measured by enzyme-linked immunosorbent assay; however, the difference between patients and control patients was not significant.…”
Section: Nervous Systemmentioning
confidence: 99%